Role of flavonoids and nitrates in cardiovascular health - Lovegrove, Julie A.; Stainer, Alex; Hobbs, Ditte A. (Proceedings of the Nutrition Society, 2017)
CVD remain the leading cause of death globally. Effective dietary strategies for their reduction are of high priority. Increasing evidence suggests that phytochemicals, particularly dietary flavonoids and nitrates, are key modulators of CVD risk reduction through impact on multiple risk factors. The aim of this review is to explore the evidence for the impact of flavonoid- and nitrate-rich foods and supplements on CVD risk, with specific reference to their importance as mediators of vascular health and platelet function. There is accumulating evidence to support benefits of dietary flavonoids on cardiovascular health. Dose-dependent recovery of endothelial function and lowering of blood pressure have been reported for the flavanol (-)-epicatechin, found in cocoa, apples and tea, through production and availability of endothelial nitric oxide (NO). Furthermore, flavonoids, including quercetin and its metabolites, reduce in vitro and ex vivo platelet function via inhibition of phosphorylation-dependent cellular signalling pathways, although further in vivo studies are required to substantiate these mechanistic effects. Hypotensive effects of dietary nitrates have been consistently reported in healthy subjects in acute and chronic settings, although there is less evidence for these effects in patient groups. Proposed mechanisms of actions include endothelial-independent NO availability, which is dependent on the entro-salivary circulation and microbial conversion of dietary nitrate to nitrite in the mouth. In conclusion, flavonoid- and nitrate-rich foods show promising effects on vascular function, yet further randomly controlled studies are required to confirm these findings and to determine effective doses.